Analysis of the Implementation of the Port Concession between KSOP Class I Sorong and PT Pelindo Regional 4 Sorong - Karubaba, Oktovianus Christian; Widarbowo, Dodik; Togatorop, Agus Leonard; Poltak, Hendra; Adiputra, Komang Hedi Pramana (International Journal of Marine Engineering Innovation and Research, 2025)
This research aims to analyze the implementation of concession policies at Sorong Port based on Government Regulation Number 31 of 2021 and Minister of Transportation Regulation Number 48 of 2021, focusing on the role of the Sorong Class I Port Authority Office (KSOP), PT Pelindo Regional 4 Sorong, and port workers. This study uses a qualitative approach with data collection techniques through interviews and field observations. The results of the study show that the implementation of concessions has provided clarity on the role between regulators and operators, but the implementation has not been optimal because there is still a gap between administrative policies and operational realization in the field. The limitations of technological infrastructure, human resource capacity, and differences in orientation between KSOP and Pelindo are the main inhibiting factors. Nevertheless, concessions have a positive impact on improving service efficiency, operational order, and the implementation of safety standards. Obstacles such as the absence of uniform Standard Operating Procedures (SOPs) and limited port facilities indicate the need for an adaptive approach that takes into account the local characteristics of the eastern region of Indonesia. This study concludes that the success of concessions at Sorong Port depends on policy harmonization, institutional coordination, and strengthening the capacity of human resources. With the support of central government policies and synergy between regulators, operators, and labor, Sorong Port has the potential to become an efficient, modern, and sustainable integrated port management model in eastern Indonesia.